Cleft lip and palate surgery in children: Anaesthetic considerations - Kwari D; Chinda J; Olasoji H; Adeosun O (Wolters Kluwer Medknow Publications, 2010)
Background: The Care of cleft patients is very challenging. Team cleft care is usually lacking in many developing countries due to shortage of qualified manpower. This study is aimed at highlighting anaesthetic challenges in the management of cleft in children. Patients and Methods: This was a study of cleft lip and palate patients who were managed during team cleft care activities at University of Maiduguri Teaching Hospital and Federal Medical Centre Nguru both in north eastern Nigeria from January to June 2009. Results: One hundred and six cleft patients presented for surgical repair under general or local anaesthesia. Fifteen (14%) patients all of whom children were unfit for general anaesthesia due to various medical reasons. Ninety-one (86%) cleft patients comprising 53(50%) children and 38(36%) adults had cleft repair under halothane general endotracheal anaesthesia and local anaesthesia, respectively. There was no anaesthetic complications recorded under local anaesthesia. Fifteen percent of children who received general endotracheal anaesthesia suffered various anaesthetic complications which included hypoxia (3.8%), laryngospasm (1.9%), kinking of endotracheal tube (5.7%), inadvertent extubation (1.9%) and pulmonary aspiration (1.9%). There was no mortality or anaesthesia-related morbidity at the time of discharge in all the cases. Conclusion: We conclude that anaesthesia for cleft lip and palate repair in hospital based team-cleft care activities in our environment is relatively safe. We recommend general anaesthesia with controlled ventilation for children and local anaesthesia for adult and older children who can cooperate.